Optimal stimulation toward the dermal papilla lineage can be promoted by combined use of osteogenic and adipogenic inducers - Taheruzzaman Kazi; Ichitaro Niibe; Akio Nishikawa; Takashi Matsuzaki (FEBS Open Bio)
Dermal papilla cells (DPCs) play crucial roles in hair regeneration, but they readily lose their hair‐forming ability during in vitro culture. Although the formation of spheroids partially restores the ability, shrinkage of the spheroids makes it difficult to maintain cellular viability. To address this problem, we stimulated DPCs with factors known to induce adipogenic and/or osteogenic differentiation, because DPCs share unique gene expression profiles with adipocytes and osteocytes. We isolated DPCs from versican (vcan)–GFP mice, in which GFP is expressed under the control of a vcan promoter, which is strongly active in DPCs of anagen hair follicles. GFP fluorescence was most intense when the spheroids were made from DPCs cultured in a half‐diluted combination of adipogenic and osteogenic media (CAO1/2), a Dulbecco’s modified Eagle’s medium‐based medium that contains 10% FBS, 275 nm dexamethasone, 2.5 mm β‐glycerol phosphate, 12.5 µg·mL−1 ascorbic acid, 0.125 µm isobutylmethylxanthine and 2.5 ng·mL−1 insulin. The dose of each additive used was less than the optimal dose for adipogenic or osteogenic differentiation, and shrinkage of the spheroids was avoided through the addition of fibroblast growth factor 2 and platelet‐derived growth factor‐AA to  CAO1/2. In addition, the gene and protein expression of vcan, osteopontin, alkaline phosphatase and α‐smooth muscle actin in the spheroids were augmented to levels similar to those of the intact dermal papillae, which exhibited restored hair‐forming activity. In conclusion, a combination of certain adipogenic and osteogenic inducers, together with fibroblast growth factor 2 and platelet‐derived growth factor‐AA, can promote differentiation toward the DPC lineage.